2017
DOI: 10.1371/journal.pone.0179946
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the probiotic Bifidobacterium animalis subsp. lactis on the non-surgical treatment of periodontitis. A histomorphometric, microtomographic and immunohistochemical study in rats

Abstract: Lactobacillus probiotics have been investigated in periodontitis. However, the effects of the genus Bifidobacterium on periodontitis are hardly known. This study evaluated the effects of the probiotic (PROB) Bifidobacterium animalis subsp. lactis (B. lactis) HN019 as an adjunct to scaling and root planing (SRP) in rats with experimental periodontitis (EP). At baseline, 32 rats were assigned to 4 groups: C (control), PROB, EP-SRP and EP-SRP-PROB. In groups EP-SRP and EP-SRP-PROB, the mandibular first molars of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1
18

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 35 publications
7
81
1
18
Order By: Relevance
“…It is known that IL-1b positively regulates the synthesis of collagenases and prostaglandins and is associated with degradation through proteases, acting directly in the process of inflammation (Bickel et al 2001). Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017. Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It is known that IL-1b positively regulates the synthesis of collagenases and prostaglandins and is associated with degradation through proteases, acting directly in the process of inflammation (Bickel et al 2001). Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017. Similar results to this study were found when probiotics were used as coadjuvants in the treatment of periodontitis (Messora et al 2016, Ricoldi et al 2017, Kobayashi et al 2017.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, the null hypothesis was rejected. Furthermore, the dose/frequency can also have an influence and 10 9 CFUs were used due to being successful in the coadjuvant treatment of periodontitis (Ricoldi et al (2017). Apical periodontitis was induced by exposing the pulp of rat molars to the oral environment allowing pulp tissue infection and culminating in pulp necrosis and subsequent AP development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only two pre‐clinical studies evaluated the effect of bacteria of the genus Bifidobacterium on periodontal disease (Oliveira et al., ; Ricoldi et al., ). Oliveira et al.…”
Section: Introductionmentioning
confidence: 99%